PERFORMANCE EVALUATION OF LEAD ACID BATTERY-BACKUP POWER SYSTEM OF SOLAR HYBRID POWER PLANT - Adera, Bayew; Sahu, Omprakash (Institute of Advanced Engineering and Science)
This work is concentrated on determining and evaluating the performance of the lead acid battery energy storage system of the solar hybrid power plant existing at Bahir Dar University. Evaluating the performance of solar battery energy storage system and other integrated units in a stand alone or grid connected solar power plants having prominent significance and contribution with respect to adapting and utilizing the indispensable solar power (PV) technology in Ethiopia. The battery performance evaluation was done by analyzing the long day performance data of the battery backup unit and by carrying out experimental discharging operation. The battery backup unit performance evaluation was done by analyzing the long day performance, the battery efficiency, charging factor, depth of discharge and capacity of the battery. The results shows that the battery was charged without being discharged a number of times. This can be the result of loss energy by self discharge of the battery, or wrong setting in recording of input output values or failure of the Xtender inverter charger RCC -02/03 recording, displaying and control units.